From Quality to Involvement: A Dual Approach to Loyalty in Beauty Events - Simanjuntak, Jerry Marmen; Rafdinal, Wahyu; Sesunan, Yunia Silvia (Integrasi Sains Media, 2025)
The rise of beauty events has generated widespread interest due to the enthusiastic participation of visitors. This study investigates the effect of event quality and personal involvement on visitor satisfaction and loyalty to beauty events. This research integrates the quality-loyalty model and the involvement-loyalty model. This research used partial least squares – structural equation model (PLS-SEM) analysis by evaluating 409 respondents who had visited beauty events. According to the study's findings, personal involvement strongly predicts satisfaction and loyalty. Furthermore, this study demonstrates that satisfaction directly influences visitor loyalty, which is consistent with contemporary theories about the formation of visitor loyalty. Theoretically, this study successfully proves the integration of the quality-loyalty model and the involvement-loyalty model in the context of loyalty toward beauty events. Practically, this study offers strategies and insights for beauty event organizers who want to create successful events and foster long-term loyalty.